The combined effect of zinc and honey to increase hemoglobin and albumin levels in white rats induced by low protein diet - Endang Sri Sunarsih; Yoga Adhi Dana; Charisha Mahda Kumala (International Journal of Advances in Applied Sciences, 2022)
Undernutrition is a type of malnutrition. Malnutrition can endanger human life, particularly that of children. Honey, which has a high nutritional value, is one of the components that can be utilized to alleviate malnutrition. Zinc tablets, in addition to honey, are thought to boost hemoglobin (Hb) and albumin levels. Zinc, as an antioxidant and catalyst for biochemical events, aids in organ healing, particularly by restoring the role of enzymes in the process of food metabolism in the body. This study was conducted as an experimental study with a pretest-posttest design and a control group. Thirty Wistar rats were randomly distributed into six groups of five rats. The average Hb and albumin levels in the group of rats differ significantly, both in the single treatment and the combination of normal rats and malnutrition control. The groups that were given zinc and honey once a day had the greatest rise in hemoglobin, which was 0.5 g/dl (3.10%). The groups who received zinc and honey twice a day had the greatest rise in albumin (1.99 g/dl) (163.11%).